Synchronous plasma membrane electrochemical potential oscillations during yeast colony development and aging - Palková, Zdena; Váchová, Libuse; Gásková, Dana; Kucerová, Helena (Molecular membrane biology, 2009)
Microorganisms that survive in natural environments form organized multicellular communities, biofilms and colonies with specific properties. During stress and nutrient limitation, slow growing and senescent cells in such communities retain vital processes by maintaining plasma membrane integrity and retaining the ability to generate transmembrane electrochemical gradients. We report the use of a Saccharomyces cerevisiae colonial model to show that population growth in a multicellular community depends on nutrient diffusion and that resting cells start to accumulate from the beginning of the second acidic phase of colony development. Despite differentiation of colony members, synchronous transmembrane potential oscillation was detected in the organized colony. The electrochemical membrane potential periodically oscillated at frequencies between those for circadian to infradian rhythms during colony aging and transiently decreased at time points previously linked with rebuilding of yeast metabolism. Despite extensive decreases in the intracellular ATP concentration and in the amount and activity of the plasma membrane proton pump during nutrient limited growth and colony aging, the transmembrane electrochemical potential appeared to be maintained above a level critical for population survival.
Keywords: Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; membránové potenciály; Membrane Potentials; Saccharomyces cerevisiae Proteins; regulace genové exprese u hub; adenosintrifosfát; Adenosine Triphosphate; Cell Membrane; elektrochemie; Electrochemistry; Gene Expression Regulation, Fungal; buněčná membrána